Three new species of the tribe Anerastiini (Lepidoptera: Pyralidae) from Korea - Choi, Sei-Woong; Jin, Da-Hee (Zootaxa, 2026)
The tribe Anerastiini in Korea comprises eight species in seven genera: Hypsotropa solipunctella, Enosima leucotaniella, Rhinaphe minor, Emmalocera venosella, Paraemmalocera gensanalis, Maliarpha borealis, Arivaca cuprella, and Arivaca gracilis. Among them, we reviewed four genera, Enosima, Polyocha, Toshitamia, and Paraemmalocera, of the tribe in Korea, and report two new species of Paraemmalocera, one new species of Polyocha, and one new record of Toshitamia for the first time in Korea. Diagnoses, adult figures, and illustrations of male and female genitalia are provided, as well as DNA Barcoding data.